Understanding Stress and Academic Adaptation: A Comparative Study of Chinese international students in Thailand - Zheng, Zhiyuan; Buarabha, Homhuan; Sriruksa, Arunee; Syers, Sikarnmanee (Journal of Ecohumanism, 2025)
Based on grounded theory, this study examines the academic adaptation stress experienced by Chinese international students in Thailand, with a comparative analysis across master’s and doctoral students, as well as students from different universities. The study categorizes the sources of academic adaptation stress and draws the following key conclusions: 1) Time management, language adaptation, student-teacher relationships, self-efficacy, and external expectations are the primary stressors for Chinese international students. 2) Master’s and doctoral students face distinct types of stress; master’s students experience greater stress related to language adaptation, while doctoral students report more stress from role conflicts and external expectations. 3) Differences in language adaptation and external expectations are found between students from Chiang Mai University (CMU) and Khon Kaen University (KKU), with KKU students experiencing relatively higher language adaptation stress. These findings have important practical implications for supporting the academic adaptation of international students.